Pancreas disease in farmed Atlantic salmon, Salmo salar L., and rainbow trout, Oncorhynchus mykiss (Walbaum), in Norway - Taksdal, T; Olsen, A B; Bjerkås, I; Hjortaas, M J; Dannevig, B H; Graham, D A; McLoughlin, M F (Journal of fish diseases, 2007)
The present paper describes, for the first time, clinical signs and pathological findings of pancreas disease (PD) in farmed Atlantic salmon, Salmo salar L., and rainbow trout, Oncorhynchus mykiss (Walbaum), in sea water in Norway. Similarities and differences with reports of PD from Ireland and Scotland are discussed. Samples of 68 rainbow trout from disease outbreaks on 14 farms and from 155 Atlantic salmon from outbreaks on 20 farms collected from 1996 to 2004 were included in the present study. The histopathological findings of PD in Atlantic salmon and rainbow trout in sea water were similar. Acute PD, characterized by acute necrosis of exocrine pancreatic tissues, was detected in nine Atlantic salmon and three rainbow trout. Salmonid alphavirus (SAV) was identified in acute pancreatic necroses by immunohistochemistry. Most fish showed severe loss of exocrine pancreatic tissue combined with chronic myositis. Myocarditis was often but not consistently found. Kidneys from 40% and 64% of the rainbow trout and Atlantic salmon, respectively, had cells along the sinusoids that were packed with cytoplasmic eosinophilic granules. These cells resembled hypertrophied endothelial cells or elongated mast cell analogues. Histochemical staining properties and electron microscopy of these cells are presented. SAV was identified by RT‐PCR and neutralizing antibodies against SAV were detected in blood samples.